1996
DOI: 10.4315/0362-028x-59.5.493
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological, Physicochemical, and Sensory Quality of Fresh Pork Chops with Low-Dose Irradiation and Modified-Atmosphere Packaging

Abstract: The combined effects of low-dose irradiation and modified-atmosphere packaging treatments were studied with respect to survival and growth of salmonellae and changes in physicochemical and sensory characteristics of fresh pork loin chops. Fresh trimmed pork loin chops were inoculated with salmonellae (about 103 to l04 CFU/g), packaged with air, vacuum, 25% CO2, 50% CO2, or 75% CO2 balanced with N2, and irradiated by 0 or 1.0 kGy electron beam. All samples were stored at 2 to 4°C for 2 weeks, followed by storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…( 1 981) reported that vacuum-packaged beef cuts irradiated at 2 kGy had improved appearance and color. Similar results also were observed in pork where irradiated, vacuum-packaged chops were redder and more color stable than irradiated, aerobically packaged chops (Luchsinger et al 1996b;Zhao et al 1996).…”
Section: Irradiationsupporting
confidence: 78%
“…( 1 981) reported that vacuum-packaged beef cuts irradiated at 2 kGy had improved appearance and color. Similar results also were observed in pork where irradiated, vacuum-packaged chops were redder and more color stable than irradiated, aerobically packaged chops (Luchsinger et al 1996b;Zhao et al 1996).…”
Section: Irradiationsupporting
confidence: 78%
“…Hence, Salmonellae was not detected in irradiated (γ-and microwave irradiation) or non-irradiated beef liver samples throughout the storage period. The microbiological examination data, of the present work, were in accordance with the microbiological safety data of shrimp and pork chops treated microwaves (19,20).…”
supporting
confidence: 85%
“…As reported (Zhao et al, 1996), irradiation of pork may result in greater drip loss than for unirradiated pork. In this study, larger drip losses were observed, but could have been caused by the added water absorbed during the dipping treatments.…”
Section: Physicochemical Changesmentioning
confidence: 82%